HUBUNGAN MOTIVASI, KEMAMPUAN, KEDISIPLINAN, DAN KEPUASAN KERJA DENGAN KINERJA MANDOR DI PT GREAT GIANT PINEAPPLE DEPARTEMEN PG 2 LAMPUNG TENGAH - Arnum Wahida Banati Husna; Wuryaningsih Dwi Sayekti; Adia Nugraha (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
The purposes of this study are to find out the level of motivation, ability, discipline, and job satisfaction, and their relationship with the performance of the foremen at PT Great Giant Pineapple Department of PG 2. This research uses a census method with 67 foremen and 19 section heads as respondents. Data collection was conducted in August to October 2019. Primary data in this study are motivation, ability, discipline, and job satisfaction, while secondary data used are foreman performance. The data are analyzed using Pearson Product Moment correlation analysis method. The results showed that motivation, discipline, and job satisfaction of the foremen are in the very high category, while the foreman's ability is in the high category.  Motivation, ability, and discipline have a positive and significant relationship with the performance of the foremen, whereas job satisfaction does not relate to the performance of the foremen. Key words: ability, discipline, job satisfaction, motivation